Use of platelet concentrate in bone regeneration through exodontics. Narrative review. - Molina Barahona, Magdalena (2023)
Introduction: The post-exodontic alveolar atrophy requires quality bone regeneration techniques, and therefore, it is necessary to apply platelet concentrates, which are bioactive agents in the process of preserving the alveolar bone. The use of platelet concentrates proved to be an excellent　osteoinducer since it leads to three important effects for maintaining bone structure. Objective:　To analyze the use of platelet concentrates in post-exodontic bone regeneration. Materials and　methods: A descriptive, explanatory study. A narrative review in which data was collected from 26 scientific articles published in scientific databases such as PubMed, Redalyc, ScienceDirect, and　Ovid between 2012 and 2022. Conclusions: Platelet concentrates are physiological materials that　speed up the healing time of post-extraction wounds. They are autologous since they are taken　from the patient him/herself, reducing the risk of postoperative reactions, and the transmission　of diseases by parenteral route. They relieve both inflammation and edema as well as post-surgery　symptoms that appear after a dental extraction. They also help to preserve the alveolar ridge,　avoiding long-term atrophy.